Limited form of wegener’s granulomatosis in a patient with Crohn’s disease. A case report - Salah, Raida Ben; Frikha, Faten; Snoussi, Mouna; Abderrahmen, Masmoudi; Hentati, Yosr; Mnif, Zeineb; Turki, Hamida; Bahloul, Zouhir (Turkish Journal of Gastroenterology, 2014)
Abstract Wegener’s granulomatosis (WG) is a multisystemic disease of unknown etiology characterized by necrotizing vasculitis and granulomatous inflammation. Although, the gastrointestinal tract can be involved in this vasculitis, the association between WG and Crohn’s disease (CD) exists and was previously described. We report the case of a 29 year-old Tunisian white patient previously diagnosed with CD, presenting 3 years later with a perforated nasal septum, mucosal ulcers and sinusitis. He had also a skin ulcerative eruption of the trunk. There was no evidence of a flare of his CD. A computed tomography scan of the head showed nasal septal perforation, and maxillary pansinusitis. A biopsy from the nasal septum demonstrated nasal mucosa with extensive necrotizing granulomatous reaction associated with vasculitis. The patient was diagnosed as having limited form of Wegener’s granulomatosis. He was treated with prednisone 60 mg/day and methotrexate 15 mg weekly. After Two months of treatment, he had no complaints, skin eruption and orofacial lesions were improved. Although, the gastrointestinal tract can be involved in patients with WG, the association with a CD exists and was previously described. The distinction between the two conditions and their possible coexistence is very important and requires histological examination of involved tissue.